A Case Study of How Visually Impaired Learners Acquire Language - Thi Minh Phuong Tran; Phuong Dzung Pho (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
The field of second language acquisition has grown enormously in the past decades. Many studies have been done on how learners acquire English as a second language; however, research on how visually impaired learners acquire English as a second or foreign language has been relatively scarce. It is even more difficult to find such studies in Vietnam. Based mainly on in-depth interviews with two visually impaired Vietnamese adults who have been successful in acquiring English, the present study seeks to answer two main questions: (1) How Vietnamese visually impaired learners acquire English as a second language; (2) What difficulties they have in learning English, and how they overcome their difficulties. The findings of the present study can contribute to the theory of second language acquisition and language teaching. The study can also provide strategies for practicing and learning a language not only for visually impaired learners but also for second language learners in general.